Relationship Between Serum Malondialdehyde (MDA) Levels With Seizure Frequency In Epilepsy Patients With Combination Of Phenytoin And Valproic Acid - Aji Noegroho; Aris Catur Bintoro; Dwi Pudjonarko (RSUP Dr. Kariadi, 2024)
Background: Oxidative stress is believed to be one of the factors involved in the pathogenesis of epileptogenic where lipid peroxidation occurs which produces Malondialdehyde (MDA). Epilepsy and some Antiepileptic Drugs (AEDs) can improve or worsen seizure frequency thereby significantly changing blood MDA levels. Objective: To determine the relationship between serum MDA levels and seizure frequency in epileptic patients treated with AEDs, a combination of phenytoin and valproic acid. Methods: A cross-sectional study with consecutive sampling of 46 subjects (with epilepsy receiving combination therapy with phenytoin and valproic acid. The research was conducted at the Neurology Policlinic at RSUP Dr. Kariadi in December 2022 – February 2023. MDA levels were measured using the Enzyme Linked Immunosorbent Assay (ELISA) method. The relationship between serum MDA levels and seizure frequency was analyzed using Spearman's test since both of the variables are ordinal scale, the results were significant if p<0.05. Results: There was no relationship between MDA levels and seizure frequency in epileptic patients with the combination of phenytoin and valproic acid. (p=0.516) There is a significant relationship between the frequency of seizures and the length of treatment (p=0.026) with a weak negative correlation (rho=0.328). There is a significant relationship between the frequency of seizures and the age of onset of epilepsy (p=0.037) with a weak negative correlation (rho=0.309). Conclusion: There is a significant relationship between the frequency of seizures with the length of treatment and the age of onset of epilepsy.